Populism as a logic of political action. (November 2019) - da Silva, Filipe Carreira; Vieira, Mónica Brito
This article offers a new understanding of populism. The argument unfolds as follows: first, the populist literature is reviewed and two main approaches are identified: ontic and logic-oriented, the more important of which is the Schmitt-Laclau logic of enmity. While the authors broadly agree with Laclau's criticism of ontic approaches, they endorse neither his ontological understanding of enmity, nor his claim that populism is politics, and enmity is the logic of populism. Next, the origins of populism are located in a paradox at the heart of democracy. Democracy defines itself as a community of inclusion, yet exclusion is constitutive of inclusion, including therefore democratic inclusion. Then is discussed what the authors believe to be the true logic of populism: resentment. Unlike enmity, which functions in Laclau's populist theory as an ontology of non-identity, resentment operates within a rivalrous framework, which presupposes identification between the parts and refers to a set of normative commitments. Finally, the article concludes by presenting an understanding of populism as a specific logic of political action.